Analyzing Income Mobility and Inequality: The Case of Argentina during the 1990’s - Albornoz, Facundo (2002)
The aim of this work is to analyze income mobility and inequality during different economic shocks in Argentina in the 1990’s, using five one-year panels: 1991/1992, 1993/1994, 1994/1995, 1998/1999, and 1999/2000. In particular, we address two questions. First, what can we say about the relationship between income mobility and the inequality cross-sectional analysis? Second, who got ahead, who fell behind and who kept up economic position during the different economic cycle facts that occurred in the 1990 decade? In other words, were the ‘upwardly mobile’, ‘immobile’ and ‘downwardly mobile’ always the same kind of individuals, or can we establish different group characteristics depending on the type of economic shock?